Restoration of Sarco/Endoplasmic Reticulum Ca2+-ATPase Activity Functions as a Pivotal Therapeutic Target of Anti-Glutamate-Induced Excitotoxicity to Attenuate Endoplasmic Reticulum Ca2+ Depletion - Zhang, Wen; Ye, Fanghua; Pang, Nan; Kessi, Miriam; Xiong, Juan; Chen, Shimeng; Peng, Jing; Yang, Li; Yin, Fei (Frontiers in Pharmacology, 2022)
Glutamate-induced excitotoxicity is a pathological basis of many acute/chronic neurodegenerative diseases. Sarco/endoplasmic reticulum Ca2+-ATPase (SERCA2b) is a membrane-embedded P-type ATPase pump that manages the translocation of calcium ions (Ca2+) from cytosol into the lumen of the endoplasmic reticulum (ER) calcium stores. It participates in a wide range of biological functions in the central nervous system (CNS). However, the role of SERCA2b in glutamate-induced excitotoxicity and its mechanism must be elucidated. Herein, we demonstrate that SERCA2b mutants exacerbate the excitotoxicity of hypo-glutamate stimulation on HT22 cells. In this study, SERCA2b mutants accelerated Ca2+ depletion through loss-of-function (reduced pumping capacity) or gain-of-function (acquired leakage), resulting in ER stress. In addition, the occurrence of ER Ca2+ depletion increased mitochondria-associated membrane formation, which led to mitochondrial Ca2+ overload and dysfunction. Moreover, the enhancement of SERCA2b pumping capacity or inhibition of Ca2+ leakage attenuated Ca2+ depletion and impeded excitotoxicity in response to hypo-glutamate stimulation. In conclusion, SERCA2b mutants exacerbate ER Ca2+-depletion-mediated excitotoxicity in glutamate-sensitive HT22 cells. The mechanism of disruption is mainly related to the heterogeneity of SERCA2b mutation sites. Stabilization of SRECA2b function is a critical therapeutic approach against glutamate-induced excitotoxicity. These data will expand understanding of organelle regulatory networks and facilitate the discovery and creation of drugs against excitatory/inhibitory imbalance in the CNS.